Nrf-2-dependent antioxidant and anti-inflammatory effects underlie the protective effect of esculeoside A against retinal damage in streptozotocin-induced diabetic rats - Nasser A., Alsabaani (2024)
Esculeoside A (ESA) is a tomato-derived glycoside with antioxidant and anti-inflammatory properties. The protective effect of ESA against diabetic retinopathy is not well-investigated and was the core objective of this study. In addition, we tested if such protection involves the activation of Nrf2 signaling. Type 1 diabetes mellitus (T1DM) was induced in adult Wistar male rats by an intraperitoneal injection of streptozotocin (65 mg/kg). Non-diabetic and T1DM rats were divided into two subgroup groups given either the vehicle or ESA (100 mg)/kg. An additional T1DM group was given ESA (100 mg/kg) and an Nrf2 inhibitor (2 mg/kg) (n=8 rats/group). Treatments continued for 12 weeks. In this study, according to the histological features, ESA improved the structure of ganglionic cells and increased the number of cells of the inner nuclear and plexiform layers in the retinas of T1DM rats. Concomitantly, it reduced the retina levels of malondialdehyde (lipid peroxides), vascular endothelial growth factor, interleukin-6, tumor necrosis factor-α, Bax, and caspase-3. In the retinas of the control and diabetic rats, ESA boosted the levels of total glutathione, superoxide dismutase, heme-oxygenase-1, and Bcl2, reduced the mRNA levels of REDD1, and enhanced cytoplasmic and nuclear levels of Nrf2. However, ESA failed to alter the mRNA levels of Nrf2 and keap1, protein levels of keap1, plasma glucose, plasma insulin, serum triglycerides, cholesterol, and LDL-c in both the control and T1DM rats. In conclusion, ESA alleviates retinopathy in T1DM rats by suppressing REDD1-associated degradation and inhibiting the Nrf2/antioxidant axis.